Trauma-Induced Coagulopathy: A Review of Specific Molecular Mechanisms - Andrea Capponi; Carlo Rostagno (Diagnostics)
Trauma remains a leading cause of death and disability in adults, and about 20% of deaths occur due to intractable bleeding. Trauma-induced coagulopathy (TIC) is a complex hemostatic disorder characterized by an abnormal coagulation response, which can manifest as either a hypo-coagulable state, leading to excessive bleeding, or a hypercoagulable state, resulting in thromboembolic events and multiple organ failure. Early diagnosis and correction of hypocoagulability may be lifesaving. Replacement of coagulation factors using blood components as well as counteracting enhanced fibrinolysis with tranexamic acid in association with a strategy of damage control are the current practices in the management of TIC. Nevertheless, the improved comprehension of the several mechanisms involved in the development of TIC might offer space for a tailored treatment with improvement of clinical outcome. This review aims to outline the pathophysiology of TIC and evaluate both established and emerging management strategies. A thorough literature review was made with a specific emphasis on articles discussing the molecular mechanisms of trauma-induced coagulopathy. We utilized PubMed, Scopus, and Web of Science with the main search terms “trauma-induced coagulopathy”, “molecular mechanisms”, and “coagulation pathways”.